Dermatologic clue to renal cell carcinoma: a case report - Chaudhary, Ajeet Singh; Tuteja, Vinay; Agarwal, M. K.; Jain, Gunja; Luniwal, Hemant (International Journal of Advances in Medicine, 2019)
Visceral malignancies often present as cutaneous lesion and are an important clue towards the diagnosis. Authors report a case of a 64 years old male, who presented to us with right hemiparesis and multiple purple-red skin lesions. Systematic evaluation, thorough history and histological examination of the skin lesion showing the characteristic lesion lead to a final diagnosis of Renal Cell Carcinoma. Although in the history and physical examination there was no sign of Renal Cell Carcinoma, but eventually the case turned out to be an extensively spread cancer. This kind of Cutaneous lesions in a case of RCC is a rare phenomenon and has not been frequently mentioned in the previous literature, thus this case reminds us about the importance of a detailed clinical look out in each and every patient and various clues to make a correct and timely diagnosis of systemic diseases. The list of visceral malignancies causing cutaneous metastasis is quite long and requires a battery of test to diagnose the same.